Temporal Dynamics of Postoperative Enterocolitis in Hirschsprung Disease: A Comparative Analysis of Earlier Onset After TAERPT versus the Duhamel Procedure - Anisa Ika Pratiwi; Nunik Agustriani; Suwardi; Ida Bagus Budhi Surya Adnyana; Henky Agung Nugroho (HM Publisher, 2026)
Background: Hirschsprung-associated enterocolitis (HAEC) remains the most formidable cause of morbidity in surgically corrected Hirschsprung disease (HD). While the transanal endorectal pull-through (TAERPT) and the Duhamel procedure are standard treatments, a critical knowledge gap exists regarding the timing of postoperative HAEC onset associated with each technique. This study aimed to investigate and compare the temporal dynamics of HAEC presentation following these distinct surgical reconstructions. Methods: This single-center, retrospective cohort study reviewed 64 HD patients who underwent either TAERPT (n=32) or a modified Duhamel procedure (n=32) between January 2022 and January 2023 at a tertiary referral hospital. The primary outcome was the incidence of severe HAEC (HAEC score ≥10). The principal secondary outcome was the time to onset of the first episode of mild-to-moderate HAEC (score <10). Due to the non-normal distribution of onset data, the Mann-Whitney U test was used for statistical comparison. Results: Baseline demographic and clinical characteristics were comparable between the two cohorts. The incidence of severe HAEC was 0% in both the TAERPT and Duhamel groups. All recorded complications were mild-to-moderate and managed non-surgically. A statistically significant and clinically profound difference in the timing of these complications was observed. The median onset of HAEC in the TAERPT group was 6.0 months (Interquartile Range [IQR], 3.0-6.0), which was significantly earlier than the median onset of 8.5 months (IQR, 3.0-24.0) in the Duhamel group (p < 0.001). The mean onset times were 5.50 ± 1.90 months and 16.09 ± 16.33 months, respectively. Conclusion: Although both TAERPT and the Duhamel procedure demonstrated excellent safety profiles regarding severe HAEC, their associated temporal patterns of mild-to-moderate enterocolitis are markedly different. The significantly earlier onset of complications following TAERPT suggests that postoperative surveillance strategies should be procedure-specific, with intensified clinical vigilance during the first postoperative year for TAERPT patients.